Assessing the effectiveness of municipal standard chart of accounts implementation : a case study of two low-capacity North West Province municipalities - Moloto, Morufa (Stellenbosch : Stellenbosch University, 2025)
Thesis (MCom)--Stellenbosch University, 2024.